Desain dan Kinerja Mesin Pemupuk Tipe Auger Bertenaga Traktor Tangan untuk Tanaman Kedelai - Diang Sagita; Wawan Hermawan; Radite Praeko Agus Setiawan (Jurnal Keteknikan Pertanian, 2018)
AbstractThe prototype of auger type fertilizer applicator powered by hand tractor has been developed. It was constructed for four planting rows of soybean in one pass. The four fertilizer applicator units were rotated by utilizing the tractor wheel axle rotation. The auger of the metering device was divided into 3 sections of auger pitch (15, 20 and 25 mm) due to the applicator could be changed the application rate. Each auger pitch represented application rate about 150 kg/ha (6 g/m), 200 kg/ha (8 g/m) and 250 kg/ha (10 g/m) respectively. The objective of this study was to develop and to conduct performance test of auger type fertilizer applicator for four planting rows of soybean that could be changed the dose. The result of stationary tests shows that the average dose for each pitch were 7.42, 9.58 and 11.60 g/auger rotation respectively at 1800 rpm (18 rpm auger) engine speed and 7.88, 9.53 and 11.49 g/auger rotation resvectively at 2000 rpm (20 rpm auger). The field test showed the result for each auger pitch were 5.91, 8.46 and 10.08 g/m respectively. These results indicated that the applicator was able to allocate fertilizer evenly with high accuracy (the error was less than 8%). The field test showed that effective field capacity was 0.137 ha/hour and efficiency was 73.7%.AbstrakPrototipe unit pemupuk tipe auger bertenaga traktor tangan untuk tanaman kedelai telah berhasil dikembangkan. Prototipe ini dibuat untuk pemupukan empat alur tanam dalam satu lintasan. Empat unit penjatah pupuk digerakkan dengan memanfaatkan putaran dari poros roda traktor. Poros auger dari metering device pupuk dibagi menjadi 3 ukuran jarak pitch yaitu 15, 20 dan 25 mm agar dosis pupuk dapatdiatur. Setiap jarak pitch auger mewakili dosis pemupukan berturut-turut 150 kg/ha (6 g/m), 200 kg/ha (8g/m), and 250 kg/ha (10 g/m). Tujuan dari penelitian ini adalah untuk mengembangkan dan menguji kinerja dari unit pemupuk kedelai empat alur tanam yang dapat diubah dosis pemupukannya. Hasil pengujian stasioner menunjukkan nilai penjatahan pupuk untuk tiap pitch berturut-turut adalah 7.42, 9.58 and 11.60 g/putaran auger saat pengujian dengan kecepatan putar engine 1800 rpm (18 rpm auger) dan 7.88, 9.53 and 11.49 g/putaran auger saat diuji pada 2000 rpm (20 rpm auger). Sementara pengujian di lahan berturutturut untuk setiap pitch adalah 5.91, 8.46 dan 10.08 g/m. Hasil tersebut menunjukkan bahwa unit pemupuktelah mampu menjatah pupuk secara merata dengan tingkat akurasi yang tinggi (error kurang dari 8%).Kapasitas lapangan efektif mesin mencapai 0.137 ha/jam dan efisiensi lapangan sebesar 73.7%.